Identification of Professional Behavior Attributes for Indonesian Medical Education - Wiwik Kusumawati, T.S Prihatiningsih, dkk (South East Asian Journal of Medical Education, 2015)
Professional Behavior (PB) is an observable behavior which reflects professional values, proven by behavior, speech and appearance that can increase patients‟ confidence of their doctor. PB is a component of professionalism which receives a lot of attention by the institution of medical education in Indonesia, with special reference to its pluralism, multicultural and multiethnic diversity. This qualitative study was conducted to identify the PB attributes adjusted for the Indonesian context. The data collection included: 1) literature study; 2) in-depth interviews and 3) Focus Group Discussions (FGD). Participants interviewed were the chairman of the Center for Pancasila Study (PSP), chairman of center for religious cross cultural studies (CRCS) , artists and Catholic, Hindu and Muslim religious leaders. Participant selection was purposeful, based on their links with the characteristic aspects of Indonesia. The FGD participants were the pertinent stakeholders and experts associated with the Medical and Health sciences education, health practitioners and physicians. Total of 26 FGD participants were grouped into 3 groups. Following analysis by the researchers, the qualitative data transcripts from FGD and interviews were randomly verified by other researchers. The qualitative data on the PB attributes from the literature and the interviews and FGDs were classified and categorized in three stages to avoid overlap, and collated to obtain the final PB attributes. The results of this study indicated the presence of 34 of 133 identified PB attributes. The five PB attributes found in all sources were: 1) respect, 2) honesty; 3) integrity; 4) responsibility and 5) altruism. There were attributes only obtained from the Indonesian sources, namely a faith or belief in God Almighty. All PB could be realized best when based on the faith in the Lord as internal motivation. Amanah, Siddiq, Tablig, and Fathonah have long been important teachings for one of the biggest religions in Indonesia (Islam) in which honesty, integrity and responsibility are implied within it, three attributes of the five essential attributes gained from this research.